2017
DOI: 10.1002/mbo3.433
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of MsmK in pathogenesis of the Streptococcus suis serotype 2

Abstract: Streptococcus suis serotype 2 (SS2) is an important swine and human pathogen that causes global economic and public health problems. Virulent S. suis strains successfully maintain high bacterial concentrations in host blood and rapidly adapt to challenging environments within hosts. Successful survival in hosts is a major factor influencing the pathogenesis of SS2. We have previously identified that SS2 colonization in mouse brain is possibly affected by the ATPase, MsmK of carbohydrate ATP‐binding cassette (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Over the last decade, multitask ATPases have been shown to play a central role in carbohydrate uptake in Firmicutes and its inactivation reduces colonization and attenuates virulence in pathogenic species 15,17,44 . To our knowledge this study is the first to show that these NBDs of ABC type I importers are functionally exchangeable between species among the Firmicutes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, multitask ATPases have been shown to play a central role in carbohydrate uptake in Firmicutes and its inactivation reduces colonization and attenuates virulence in pathogenic species 15,17,44 . To our knowledge this study is the first to show that these NBDs of ABC type I importers are functionally exchangeable between species among the Firmicutes.…”
Section: Discussionmentioning
confidence: 99%
“…Copper efflux [20] PmtA Ferrous iron and cobalt efflux, tolerance to hydrogen peroxide-induced oxidative stress [21] MsmK Utilization of multiple carbohydrates, pathogenesis [22,23] Ide Ssuis Degradation of porcine IgM, complement evasion [24][25][26] IgdE Degradation of porcine IgG [27] IgA1 protease/ZmpC Degradation of human IgA1, pathogenesis 1 [28][29][30][31] eSTK Maintaining bacterial morphology, tolerance to stresses, pathogenesis [32][33][34] eSTP Virulence, cell adhesion, and immune evasion 2 [35,36] SspA-1 Virulence, trigger of proinflammatory cytokines [37,38] SspA-2 Pathogenesis, proinflammatory response in macrophages [39][40][41] Superoxide dismutase Oxidative stress resistance, virulence [42,43] NADH oxidase Tolerance to oxidative stress, virulence [44,45] SsnA Degradation of human and porcine neutrophil extracellular traps, pathogenesis [46][47][48] EndAsuis Degradation of neutrophil extracellular traps [49] Enolase Binding of extracellular matrix components, pathogenesis [50][51][52][53][54][55][56][57][58] LuxS Growth, biofilm formation, capsule synthesis, hydrogen peroxide resistance, resistance to fluoroquinolones, pathogenesis [59]…”
Section: Copamentioning
confidence: 99%
“…Zhu et al [60] demonstrated that (p)ppGpp synthetases that mediate adaptive response of bacteria), could regulate the growth and pathogenicity of S. suis. Tan et al [61] demonstrated that MsmK, an ATPase of ATP-binding cassette (ABC) transporters, is a multifunctional factor that not only plays an important role in carbohydrate utilization by S. suis, but also contributes to its resistance to blood killing, phagocytosis, and osmotic stress, increases haemolytic activity and biofilm formation and promotes ability of the pathogen to infect the hosts.…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…The presence of biofilms in biomaterials used in surgery (e.g. vascular catheters, prosthetic joints and artificial heart valves) is one of the main causes of difficult-to-cure infections [3,6,61,83,84].…”
Section: Importance Of Biofilm Formationmentioning
confidence: 99%